Apakah Penggunaan Kredit UKM di Kota Denpasar Sudah Efektif? - Adyatma, I Wayan Chandra (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No.1, Februari 2018 (pp. 1-144), 2018)
This Study had purpose to (1) analyze the magnitude of the effective use of SME loans in Denpasar, Bali Province, (2) analyze the effect of credit priority, level of education, training, credit period, and the amount of credit on the return of credit, (3) analyze the effect of credit priority, level of education, training, credit period, the amount of credit, and the rate of return of loans to the effectiveness of the use of credit, (4) analyze the effect of indirect sales, level of education, training, credit period, and the amount of credit to the effectiveness of the use of credit, through rate credit repayment.  The technique that used is descriptive analysis and inferential statistics using path analysis. The conclusion of this study were (1) the effectiveness of the use of high credit mostly in the SME sector of the trade. (2) The calculation direct relationship on the return of credit, there are two variables: the number of sales and training were not significant on the return of credit, (3) In direct relation to the effectiveness of the use of positive and significant impact. (4) The calculation indirectly indicates that the all variable through credit back level as an intervening variable that strengthen the relationship.
Keywords: UKM (usaha kecil menengah), efektivitas, pengembalian kredit, penjualan, pendidikan, pelatihan, jangka waktu, jumlah kredit.